ZOOPLANKTON DIVERSITY AND PHYSICOCHEMICAL PARAMETERS OF HIRAN RIVER AND A VERAVAL COASTAL REGION, GUJARAT, INDIA - POOJA M. KUVADIYA; JATIN V. RAVAL; AGNI VYAS (The Bioscan, 2020)
Qualitative analysis of zooplankton besides physicochemical parameters of water was carried out during the study. In the present study, we had compared the relationship between zooplankton diversity and water quality parameters of Hiran River and Veraval Coastal area. The present study was carried out from September 2019 to February 2020. In the current investigation, impact of different physicochemical parameters on zooplankton population was investigated. Data analysis highlighted significant difference in zooplankton abundance among the various types of water body. During the study parameters like pH, TS, TSS, TDS, DO, BOD, Total hardness, Ca ++ hardness, Mg ++ hardness, Electric conductivity, Na and K were recorded. Zooplanktons are bio-indicators of water ecosystems. Their diversity depends on the water conditions. They play an integral role in transfer of energy to the consumers hence they form the second tropic level in the energy flow. The findings of the present study provide useful knowledge on the spatial organization of zooplankton diversity in different types of water bodies.